Increased fibrosis progression rates in hepatitis C patients carrying the prothrombin G20210A mutation - Maharshak, Nitsan (Baishideng Publishing Group Co., Limited, 2011)
AIM: To examine whether hepatitis C virus (HCV)-infected patients who carry hypercoagulable mutations suffer from increased rates of liver fibrosis. METHODS: We analyzed DNA samples of 168 HCV patients for three common hypercoagulable gene mutations: prothrombin 20210 (PT20210), factor V Leiden (FV Leiden) and methylene tetrahydrofolate reductase (MTHFR). The patients were consecutively recruited as part of the prospective “Fibroscore Study” in France. The effect of the various mutations on the rate of fibrosis was analyzed statistically and was correlated with epidemiological, clinical and biochemical data such as grade and stage of liver biopsies, patients’ risk factors for liver cirrhosis, and timing of infection. RESULTS: Fifty two of the patients were categorized as “fast fibrosers” and 116 as “slow fibrosers”; 13% of the “fast fibrosers” carried the PT20210 mutation as compared with 5.5% of the “slow fibrosers”, with an odds ratio of 4.76 (P = 0.033; 95% CI: 1.13-19.99) for “fast” liver fibrosis. Carriage of MTHFR or FV Leiden mutations was not associated with enhanced liver fibrosis. CONCLUSION: Carriage of the PT20210 mutation is related to an increased rate of liver fibrosis in HCV patients.